(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article analyzes the psychological and pedagogical characteristics that emerge during the professional self-development of future teachers. It emphasizes that students and young specialists entering the teaching profession should not only acquire theoretical knowledge and practical skills but also develop personal qualities, think independently, maintain professional motivation, and be prepared for continuous self-improvement. Psychological aspects such as self-awareness, internal reflection, emotional stability, and social adaptability are explored in detail. The article highlights the importance of harmonizing both psychological and pedagogical dimensions in preparing well-rounded and competent future educators.